INCREASING TEACHERS' CREATIVITY THROUGH THE DEVELOPMENT OF ORGANIZATIONAL CULTURE, EMPOWERMENT AND VISIONARY LEADERSHIP OF SCHOOL PRINCIPLES - Makhrus, Makhrus; Sunardi, Oding; Retnowati, Rita (IJOSMAS, 2022)
Teacher creativity in the learning process is actions that are deliberately taken by teachers to develop, convey and use new or different ideas from before in carrying out interactive, interesting and effective learning activities so as to improve learning outcomes.Based on the preliminary survey data, the above conditions can be concluded that the creativity of State MTs teachers in the work environment of the Ministry of Religion of East Jakarta City is still low. Therefore it needs to be upgraded to a better stage. However, the improvement in question, especially in terms of increasing teacher creativity, requires sufficient time because it is related to various factors that influence it. These factors include; organizational culture, empowerment and visionary leadership of school principals. The population in this study were PNS MTs Negeri teachers in the East Jakarta City area, totaling 622 people from 17 schools. The sampling technique used is a random sampling technique (proportional random sampling). Samples were taken using the Taro Yamane formula with a sampling error rate of 5%. The results of the calculation of the number of samples are 243 people.The results showed: 1) There is a positive relationship between organizational culture and teacher creativity so that strengthening organizational culture can increase teacher creativity, 2). There is a positive relationship between empowerment and teacher creativity so that strengthening empowerment can increase teacher creativity, 3). There is a positive relationship between school principal's visionary leadership and teacher creativity so that strengthening principal's visionary leadership can increase teacher creativity, 4). There is a positive relationship between organizational culture and empowerment together with teacher creativity so that strengthening organizational culture and empowerment together can increase teacher creativity, 5). There is a positive relationship between organizational culture and the principal's visionary leadership together with the creativity of teachers so that the strengthening of organizational culture and the principal's visionary leadership together can increase the creativity of teachers, 6). There is a positive relationship between empowerment and visionary leadership of school principals together with teacher creativity so that strengthening empowerment and visionary leadership of principals together can increase teacher creativity, 7) There is a positive relationship between organizational culture, empowerment and visionary leadership of principals collectively. together have a positive relationship with teacher creativity so that strengthening organizational culture, empowerment and visionary leadership of school principals together can increase teacher creativity